2022
DOI: 10.1186/s12876-022-02260-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear respiratory factor 1 promotes the growth of liver hepatocellular carcinoma cells via E2F1 transcriptional activation

Abstract: Background Recent studies have shown that functional mitochondria are essential for cancer cells. Nuclear respiratory factor 1 (NRF1) is a transcription factor that activates mitochondrial biogenesis and the expression of the respiratory chain, but little is known about its role and underlying mechanism in liver hepatocellular carcinoma (LIHC). Methods NRF1 expression was analyzed via public databases and 24 paired LIHC samples. Clinical-pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…High expression of NRF1 in HCC tissues is associated with poor prognosis of HCC patients [ 46 ]. Consistent with the previous reports [ 45 , 46 ], our results demonstrated that NRF1 expression was up-regulated in HCC tissues and cells, and its high expression predicted a poor prognosis of HCC patients. SPIDR, also known as KIAA0146, functions in homologous recombination repair of DNA double-strand breaks [ 31 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…High expression of NRF1 in HCC tissues is associated with poor prognosis of HCC patients [ 46 ]. Consistent with the previous reports [ 45 , 46 ], our results demonstrated that NRF1 expression was up-regulated in HCC tissues and cells, and its high expression predicted a poor prognosis of HCC patients. SPIDR, also known as KIAA0146, functions in homologous recombination repair of DNA double-strand breaks [ 31 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nuclear respiratory factor 1 (NRF1) is a key factor in the activation of genes involved in the regulation of cellular metabolism and mitochondrial biogenesis [ 43 , 44 ]. NRF1 promotes cell growth by transcriptionally activating E2F1 in HCC [ 45 ]. High expression of NRF1 in HCC tissues is associated with poor prognosis of HCC patients [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of ChIP-Seq datasets shows that the ChIP-Seq identified NRF1 target genes in SK-N-SH cells are involved in various cellular processes such as mitochondrial function, RNA metabolism, DNA damage repair, cell cycle regulation, protein translation initiation, and ubiquitin-mediated protein degradation ( 42 ). Aberrant NRF1 has been linked to tumorigenesis, as some key oncogenes are regulated by NRF1, including genes related to glioblastoma ( 43 ), breast tumorigenesis ( 44 , 45 ), bladder cancer ( 46 ), prostate cancer ( 47 ), liver hepatocellular carcinoma ( 48 ) and EBV-associated gastric cancer ( 49 ). Therefore, in addition to being a crucial transcription factor, NRF1 has also emerged as a valuable biomarker for cancer diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some lncRNAs were found to form complex with NRF1 to activate mitochondrial biogenesis in HCC [ 55 ] and colorectal cancer patients [ 56 ]. NRF1 was also found to activate E2F1 as a transcription factor to promote HCC proliferation by a ChIP-seq analysis for NRF1 target genes [ 57 ]. Similarly, the knock-down of TFAM could promote cancer progression according to bioinformatic databases of 18 head and neck cancer cases [ 58 ] as well as ovarian cancer [ 59 ].…”
Section: Roles Of Mitochondrial Dynamics In Maintaining Mitochondrial...mentioning
confidence: 99%